Knowledge, attitude, and practices about contraceptive in Western Rajasthan, India - Aseri, Gayatri; Agrawal, Sudesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: This study was carried out to assess the knowledge, attitude, and practice of contraceptive methods among women attending a tertiary care hospital in Western Rajasthan. Methods: This cross-sectional study was conducted in the department of obstetrics and gynecology, PBM and the associated group of hospitals, attached to Sardar Patel Medical College, Bikaner, Rajasthan, India. Total 500 married women between age group 15-49 yrs were included. These all women interviewed using a structured questionnaire after approval of the hospital’s ethical committee. Results: Total 500 women interviewed for their knowledge, attitude, and practices about contraception. Out of which, 402 (80.4%) women had some knowledge of at least one contraception method at the time of the study. The most common sources of information about contraception were husband and family member. Amongst the various contraceptives most commonly known was condom (78.4%). Only 265 (53%) women were practicing contraception at present. Most commonly used contraceptive was condom (40.8%). The most common reason for the non-practice of contraception was need of more child or male child in 34.8% families followed by opposition from in-laws (12.4%). Conclusions: Literacy was positively associated with family planning related knowledge and practices. Preconception knowledge and practices about contraception are poor in our study population. Many of the women were getting MTP pills over the counter without consulting to health care persons and then later presents with complications.